2014
DOI: 10.1002/ajpa.22594
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Lactase persistence and dairy intake in Mapuche and Mestizo populations from southern Chile

Abstract: Lactase persistence (LP) occurs at a very low frequency in indigenous populations from Latin America, offering an opportunity to understand the relationship between this genetic trait and patterns of dairy consumption. Here, the frequency of LP is analyzed from Mapuche and -an adjacent- mestizo population inhabiting the Araucanía region. In addition to genotyping for LP, participants were surveyed in relation to general perception and consumption habits of dairy products. Low LP frequency (10%) and very low da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In our study, 35% of patients had LP‐related genotype. In Chile, several publications have shown a prevalence of LP‐related genotype in general population between 40% and 57%, and only 10% in Chilean Amerindian population, being the C>T ‐13910 SNP the main determinant of LP/LNP in our population . The usefulness of the genetic test for determination of the LP/LNP phenotype has the main difficulty that concordance between genetics and phenotype depends on age.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, 35% of patients had LP‐related genotype. In Chile, several publications have shown a prevalence of LP‐related genotype in general population between 40% and 57%, and only 10% in Chilean Amerindian population, being the C>T ‐13910 SNP the main determinant of LP/LNP in our population . The usefulness of the genetic test for determination of the LP/LNP phenotype has the main difficulty that concordance between genetics and phenotype depends on age.…”
Section: Discussionmentioning
confidence: 89%
“…Although dairy consumption has countless benefits for improving health issues, the amount of dairy intake is lower than the international recommendations [22][23][24]29], which can lead to an increase in the incidence of certain diseases such as osteoporosis, diabetes, colorectal cancer, and hypertension as well as healthcare costs [30]. In order to identify policy options to increase dairy intake, reviewing successful community-based strategies and their effectiveness is needed to help policy-makers in choosing the best policy options with respect to situations in each country.…”
Section: Introductionmentioning
confidence: 99%
“…According to the United States Department of Agriculture (USDA), the daily recommendation of dairy for an adult with an energetic need of 2000 Kcal/day is 3 portions per day, but the US population only consumes half of the recommendation (1.5 portions per day) [18]. Also, some other studies conducted in different age groups indicated that the intake was below the recommended daily amount of dairy [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, diverse studies carried out in Brazil, Ecuador, Colombia, Peru, and Chile found the C/T‐13910 SNP to be the most frequent polymorphism associated with LP. However, T‐13910 allele frequency varies greatly depending on ethnic affiliation or genetic ancestry background of the population or individuals studied, being higher when European contribution increases (Fernández & Flores, 2014; Friedrich, Santos, et al, 2012; Guimarães Alves et al, 2021; Mattar et al, 2009; Mendoza Torres et al, 2012; Paz y Miño et al, 2016). Association between expected lactose digestion phenotype considering C/T‐13910 genotype, and the effectively observed phenotype, was assessed in some studies in South America.…”
Section: Introductionmentioning
confidence: 99%